Intravenous Artesunate for the Treatment of Severe Imported Malaria: Implementation, Efficacy, and Safety in 1391 Patients. (13th February 2021) - Roussel, Camille; Ndour, Papa Alioune; Kendjo, Eric; Larréché, Sébastien; Taieb, Aida; Henry, Benoît; Lebrun-Vignes, Bénédicte; Chambrion, Charlotte; Argy, Nicolas; Houzé, Sandrine; Mouri, Oussama; Courtin, David; et al.
Abstract: Background: Intravenous artesunate is the World Health Organization–recommended first-line treatment for severe malaria worldwide, but it is still not fully licensed in Europe. Observational studies documenting its safety and efficacy in imported malaria are thus essential. Methods: We prospectively collected clinical and epidemiological features of 1391 artesunate-treated patients among 110 participant centers during the first 7 years (2011–2017) of a national program implemented by the French Drug Agency. Results: Artesunate became the most frequent treatment for severe malaria in France, rising from 9.9% in 2011 to 71.4% in 2017. Mortality was estimated at 4.1%. Treatment failure was recorded in 27 patients, but mutations in the Kelch-13 gene were not observed. Main reported adverse events (AEs) were anemia (136 cases), cardiac events (24, including 20 episodes of conduction disorders and/or arrhythmia), and liver enzyme elevation (23). Mortality and AEs were similar in the general population and in people with human immunodeficiency virus, who were overweight, or were pregnant, but the only pregnant woman treated in the first trimester experimented a hemorrhagic miscarriage. The incidence of post-artesunate–delayed hemolysis (PADH) was 42.8% when specifically assessed in a 98-patient subgroup, but was not associated with fatal outcomes or sequelae. PADH was twice as frequent in patients of European compared with African origin. Conclusions: Artesunate was rapidly deployed and displayed a robust clinical benefit in patients with severe imported malaria, despite a high frequency of mild to moderate PADH. Further explorations in the context of importation should assess outcomes during the first trimester of pregnancy and collect rare but potentially severe cardiac AEs. Abstract : From 2011, artesunate was deployed in France through a specific program streamlined by prepositioning in hospital pharmacies to treat severe imported malaria. Robust clinical benefit was confirmed in 1391 patients, as in several subgroups. Anemia was the commonest adverse event.